Robust Piezo Impedance Magnitude Measurement Method - Saar, T. (Elektronika ir Elektrotechnika, 2011)
Piezo impedance spectroscopy is widely used in structural health monitoring (SHM) applications. Purpose of the research was tofind most robust and cheap method for impedance magnitude measurement. Proposed system consists of analog front end (AFE), signalsynthesizer and microcontroller unit. AFE enables to use low sampling rate, while using high frequency excitation signal. Proposedsystem uses chirp excitation signal in 20kHz- 600kHz frequency range. Results were compared against measurements made withcommercial impedance analyzer. Results show great potential for this method in SHM applications. Ill. 6, bibl. 10 (in English; abstractsin English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.623